Republic Of Poland : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
The Selected Issues paper and Statistical Appendix assesses the prospects of future capital flows to Poland. The paper briefly reviews the theory behind capital flows, and presents the stylized facts of recent capital flows to Poland. It reviews the experience of other large-scale privatizers, and looks at the empirical determinants of capital flows. The paper also reviews the development of foreign currency loans in Poland, drawing comparisons with other emerging market economies, and discusses challenges posed by these loans.